Dopaminergic axon guidance: which makes what? - Prestoz, Laetitia; Jaber, Mohamed; Gaillard, Afsaneh (Frontiers in Cellular Neuroscience, 2012)
Mesotelencephalic pathways in the adult central nervous system have been studied in great detail because of their implication in major physiological functions as well as in psychiatric, neurological, and neurodegenerative diseases. However, the ontogeny of these pathways and the molecular mechanisms that guide dopaminergic axons during embryogenesis have been only recently studied. This line of research is of crucial interest for the repair of lesioned circuits in adulthood following neurodegenerative diseases or common traumatic injuries. For instance, in the adult, the anatomic and functional repair of the nigrostriatal pathway following dopaminergic embryonic neuron transplantation suggests that specific guidance cues exist which govern embryonic fibers outgrowth, and suggests that axons from transplanted embryonic cells are able to respond to theses cues, which then guide them to their final targets. In this review, we first synthesize the work that has been performed in the last few years on developing mesotelencephalic pathways, and summarize the current knowledge on the identity of cellular and molecular signals thought to be involved in establishing mesotelencephalic dopaminergic neuronal connectivity during embryogenesis in the central nervous system of rodents. Then, we review the modulation of expression of these molecular signals in the lesioned adult brain and discuss their potential role in remodeling the mesotelencephalic dopaminergic circuitry, with a particular focus on Parkinson's disease (PD). Identifying guidance molecules involved in the connection of grafted cells may be useful for cellular therapy in Parkinsonian patients, as these molecules may help direct axons from grafted cells along the long distance they have to travel from the substantia nigra to the striatum.